A influência do Top of Mind no Brand Equity: um estudo sobre marcas de uísque - Odone, Giuliano Mearim (2018)
The present study main topic is the measure of brand equity using a consumer based model. It investigates the existence of a hierarchy of forces that influence BE formation. The research also includes the influence of spontaneous brand awareness (top of mind - TOM) on BE, and brand recommendation. To apply such model, a survey with 679 consumers from São Paulo, to measure the brand equity assigned to two of the main whisky brands in Brazil - Johnnie Walker Red Label e Jack Daniels. The development occurred in two stages. First, a thorough review of the theories that measure brand equity, brand loyalty and brand awareness. The second stage, involved the data collection via a survey and its analysis. The results show that there is a hierarchy of forces that form BE, and TOM has a positive influence on it, and BE precedes brand recommendation. The study has important contributions to the academy since it includes spontaneous brand awareness on BE measurement, while the other scales use only aided brand awareness. Also, the survey was applied with a great variety of consumer profiles, therefore, has outmost importance on the validation of the BE measurement model with high value brands in the Brazilian market.